The Foundations of Family Life Education Model: Understanding the Field. Issue 3 (30th July 2019) - Darling, Carol A.; Cassidy, Dawn; Rehm, Marsha
Abstract : Implementation of family life education (FLE) can positively influence individual and family well‐being by helping families to help themselves. However, because the nature of FLE is not widely understood, a comprehensive model highlighting and integrating fundamentals of the practice is needed. The foundations of family life education model (FFLE) is a visual illustration that incorporates foundational principles of FLE with changes in culture, context, content, practice, and family well‐being across time. In addition to the visual representation of core concepts defining FLE and their relationship with each other, the model provides a unique conceptualization by reframing the frequently referenced 10 content areas as concepts within the content, context, and practice of the field. The creation of a graphic identity for the practice of FLE can offer greater clarity and understanding regarding the nature of FLE, thereby increasing opportunities for implementation and best practices.